Analisis Semiotika Roland Barthes pada Iklan Good Day Coffee Versi “Rizky Febian & Tiara Andini” - Al Gadri, Henri Henriyan (Jurnal Artikula, 2022)
This study discusses the semiotic analysis of Roland Barthes' theory which includes three dimensions, namely Denotation, Connotation and Myth (myth). The purpose of this study was to determine the meaning of denotation, connotation and myths in the Good Day Coffee advertisement. The research results obtained by Good Day Coffee version "Rizky Febian & Tiara Andini" are considered good, interesting, creative, liked by consumers, enhance character, easy to remember, and describe the message of Good Day Coffee in general. As a beverage product, Good Day Coffee is considered quite successful in marketing. Good Day Coffee advertisements also often appear on television, especially during broadcast hours of featured television programs, one of which is the "Rizky Febian & Tiara Andini" version of the Good Day Coffee advertisement, the meaning of the advertisement can be seen using Roland Barthes' theory.